Ownership structure and corporate social responsibilities disclosures in Malaysian companies - Abdul Wahid Mohd Kassim; Raman Noordin; Junaidah Jaidi; Sulaiman Tahajuddin (Penerbit UMS, 2021)
This paper investigates the link between Ownership Structure and the quantity of CSR in annual reports. This study used content analysis and a dataset from Malaysian companies listed in Bursa Malaysia. The results based on the full regression model with three variables Managerial ownership, Government ownership, and Foreign ownership. The findings of this study indicated that two variables, Government ownership and Foreign ownership is associated with the extent of CSRD. The other predictive variable, Managerial ownership was found to be significant but not in the predicted direction. Thus, the hypothesis was not supported.